Evaluasi Kebijakan Disiplin Pegawai Negeri Sipil Di Kantor Lurah Patih Galung Kota Prabumulih Provinsi Sumatera Selatan - Hadi, Sopyan; Putra, Raniasa; muftizar, akhmad (Journal of Law & Policy Review, 2023)
This article aims to describe and analyze the evaluation of civil servant discipline policies and determine the causes of civil servant disciplinary violations at the Patih Galung sub-district office. This research uses a qualitative research approach involving 11 informants. The data collection techniques used in this research are observation, interviews and documentation studies. The research results show that the evaluation of civil servant discipline policies at the Patih Galung Village Head Office, Prabumulih City, shows an increase in discipline since the implementation of PP 53 of 2010, although it is not yet optimal. Key factors such as organizational culture, supervision, incentives, sanctions, and effective leadership play an important role. However, challenges such as leadership assertiveness and lack of socialization still exist. Further efforts are needed to improve communication, resource management, disposition, and bureaucratic structure to achieve optimal discipline.